Operative techniques in laparoscopic colorectal surgery - Delaney, C. P. (Conor Patrick); Lawrence, Justin K.; Keller, Deborah S.; Champagne, Bradley J.; Senagore, Anthony J., 1958- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"The Second Edition of Operative Techniques in Laparoscopic Colorectal Surgery is designed to give surgeons the learning tools they need to understand and successfully incorporate laparoscopic colorectal surgery into their practice. Because of the steep learning curve for this technique, this edition goes to great lengths to cover every aspect of each procedure in great detail -- even including the pitfalls to avoid. To help the reader with pattern-recognition, detailed, four-color photographs of important landmarks have been incorporated for them to review. Plus, an edited video is included to provide clear, step-by-step instruction of each procedure. Surgeons need appropriate training before incorporating laparoscopic colorectal surgery into their practice. This book will be a useful resource for residents, fellows in training, and surgeons who are either attending courses in laparoscopic colorectal surgery or are at an early stage of integrating this technique into their practice. FEATURES: Chapters contain a detailed textual description of procedural steps and common pitfalls Includes sections on management of intraoperative complications and other useful tips All new major operative videos Includes an expanded list of colorectal procedures New chapters include Mobilization of the Mesorectum, Handsewn Coloanal Anastomosis, Robotic Single-port Right Colonectomy, Single Port Total Colectomy with End Ileostomy, Robotic Low Anterior Resection"--